ANALISIS PEMBELAJARAN BERBASIS JOYFUL LEARNING DENGAN KEMAMPUAN BERPIKIR KREATIF PADA MATA PELAJARAN IPAS SISWA SD (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning in elementary schools needs to be designed in an innovative and enjoyable way to increase student engagement and develop creative thinking skills. However, in practice, learning is often still teacher-centered, limiting students' opportunities to express creative ideas and opinions. This study aims to analyze joyful learning-based instruction and its relationship with students' creative thinking abilities in the IPAS subject at the elementary school level. The method used in this study is a literature review by analyzing various national and international journal articles published between 2021 and 2026, which were obtained through searches on Google Scholar. The data were analyzed descriptively to identify research findings related to the implementation of joyful learning and the development of students' creative thinking skills. The results of the review indicate that joyful learning-based instruction can create an active, enjoyable, and meaningful learning environment that increases students’ motivation and engagement in IPAS learning. In addition, this approach contributes to the development of students' creative thinking skills, including fluency, flexibility, originality, and elaboration. Therefore, joyful learning can be considered an effective instructional strategy to support the development of creative thinking skills among elementary school students.